Erythroferrone inhibits the induction of hepcidin by BMP6 - Arezes, J; Foy, N; McHugh, K; Sawant, A; Quinkert, D; Terraube, V; Brinth, A; Tam, M; Lavallie, E; Taylor, S; Armitage, A; Pasricha, S; et al. (American Society of Hematology, 2018)
Decreased hepcidin mobilizes iron, which facilitates erythropoiesis, but excess iron is pathogenic in beta-thalassemia. Erythropoietin (EPO) enhances erythroferrone (ERFE) synthesis by erythroblasts, and ERFE suppresses hepatic hepcidin production, through an unknown mechanism. The BMP/SMAD pathway in the liver is critical for control of hepcidin, and we show that EPO suppressed hepcidin and other BMP target genes in vivo in a partially ERFE-dependent manner. Furthermore, recombinant ERFE suppressed the hepatic BMP/SMAD pathway independently of changes in serum and liver iron, and in vitro, ERFE decreased SMAD 1/5/8 phosphorylation and inhibited expression of BMP target genes. ERFE specifically abrogated the induction of hepcidin by BMP5, BMP6 and BMP7, but had no or little effect on hepcidin induction by BMP2, 4, 9 or Activin B. A neutralising anti-ERFE antibody prevented the ability of ERFE to inhibit hepcidin induction by BMP5, BMP6 and BMP7. Cell-free HTRF assays showed that BMP5, BMP6 and BMP7 competed with anti-ERFE for binding to ERFE. We conclude that ERFE suppresses hepcidin by inhibiting hepatic BMP/SMAD signalling via preferentially impairing an evolutionarily closely related BMP sub-group of BMP5, BMP6 and BMP7. ERFE can act as a natural ligand trap generated by stimulated erythropoiesis in order to regulate availability of iron.